Nanofiber Fuel Cell MEAs with a PtCo/C Cathode. Issue 7 (1st January 2019) - Slack, J. J.; Gumeci, C.; Dale, N.; Parrondo, J.; Macauley, N.; Mukundan, R.; Cullen, D.; Sneed, B.; More, K.; Pintauro, P. N.
Abstract : PtCo/C and Pt/C catalyst powders were incorporated into electrospun nanofiber and conventional sprayed cathode membrane-electrode-assemblies (MEAs) at a fixed electrode loading of 0.1 mgPt /cm 2 . The binder for PtCo/C nanofiber cathodes and Pt/C nanofiber anodes was a mixture of Nafion and poly(acrylic acid) (PAA), whereas the sprayed electrode MEAs utilized a neat Nafion binder. The structure of electrospun fibers was analyzed by scanning transmission electron microscopy (STEM) and energy-dispersive X-ray spectroscopy (EDS), which showed that the fibers were ∼30% porous with a uniform distribution of catalyst and binder in the axial and radial fiber directions. The initial performance of nanofiber MEAs at 80°C was 20% better than the sprayed electrode MEA (a maximum power density of 1, 045 mW/cm 2 vs. 869 mW/cm 2 ). The benefit of the nanofiber electrode morphology was most evident at end-of-test (after a metal dissolution accelerated stress test), where power densities dropped by only 8%, after 30, 000 square wave voltage cycles (0.6 V to 0.95 V), as compared to a 35% drop in the maximum power for the sprayed electrode MEA. The use of a recovery protocol improved the initial performance of a nanofiber MEA by ∼13%, to 1, 070 mW/cm 2 at 0.65 V, and increased the power after a metal dissolution stress test by 5–10% (e.g. 840 mW/cm 2 at 0.65 V after 30, 000 voltage cycles). At rated power, the nanofiber MEA generated more than 1, 000 mW/cm 2 at 99°C and a pressure of 250 kPaabs. The high performance and durability of PtCo/C nanofiber cathode MEAs is due to the combined effects of a highly active cathode catalyst and the unique nanofiber electrode morphology, where there is a uniform distribution of catalyst and binder (no agglomeration) and short transport pathways across the submicron diameter fibers (which lowers gas transfer resistance and facilitates water removal from the cathode).